Flash survey on severe acute respiratory syndrome coronavirus-2 infections in paediatric patients on anticancer treatment. (June 2020) - Hrusak, Ondrej; Kalina, Tomas; Wolf, Joshua; Balduzzi, Adriana; Provenzi, Massimo; Rizzari, Carmelo; Rives, Susana; del Pozo Carlavilla, María; Alonso, Maria E.V.; Domínguez-Pinilla, Nerea; Bourquin, Jean-Pierre; Schmiegelow, Kjeld; et al.
Abstract: Introduction: Since the beginning of COVID-19 pandemic, it is known that the severe course of the disease occurs mostly among the elderly, whereas it is rare among children and young adults. Comorbidities, in particular, diabetes and hypertension, clearly associated with age, besides obesity and smoke, are strongly associated with the need for intensive treatment and a dismal outcome. A weaker immunity of the elderly has been proposed as a possible explanation of this uneven age distribution. Thus, there is concern that children treated for cancer may allso be at risk for an unfavourable course of infection. Along the same line, anecdotal information from Wuhan, China, mentioned a severe course of COVID-19 in a child treated for leukaemia. Aim and methods: We made a flash survey on COVID-19 incidence and severity among children on anticancer treatment. Respondents were asked by email to fill in a short Web-based survey. Results: We received reports from 25 countries, where approximately 10, 000 patients at risk are followed up. At the time of the survey, more than 200 of these children were tested, nine of whom were positive for COVID-19. Eight of the nine cases had asymptomatic to mild disease, and one was just diagnosed with COVID-19. We also discuss preventive measures that are in place or should be taken and treatment options in immunocompromised children with COVID-19. Conclusion: Thus, even children receiving anticancer chemotherapy may have a mild or asymptomatic course of COVID-19. While we should not underestimate the risk of developing a more severe course of COVID-19 than that observed here, the intensity of preventive measures should not cause delays or obstructions in oncological treatment. Highlights: Flash survey was used to get data on COVID-19 incidence and severity. Paediatric haematology/oncology departments of 25 countries responded. COVID-19 may have a mild course in these immunocompromised children. Precautions should be taken to prevent any infections including COVID-19. Malignancy is a primary danger; preventive measures should not hinder its treatment.